Country of origin and country of service delivery effects in transnational higher education: a comparison of international branch campuses from developed and developing nations. Issue 1 (2nd January 2016) - Chee, Chiu Mei; Butt, Muhammad Mohsin; Wilkins, Stephen; Ong, Fon Sim
ABSTRACT: Over the last decade, international branch campuses have been established by universities from developing countries as well as developed countries. Little research has been conducted into students' perceptions of branch campuses from different countries, or how universities from different countries compete in the increasingly competitive market. A framework incorporating the concepts of country of origin and country of service delivery is adopted to assess how potential undergraduate students in Malaysia perceive the home and international branch campuses of universities from the United Kingdom (UK) and India, which are used to represent universities from developed and developing nations. It was found that for a university from a developing nation, students perceived the image, reputation, quality and brand equity of its home campus more positively than its international branch campus. The results suggest that although all universities must devise and implement strategies that enhance the image and reputation of their international branch campuses, institutions from developing countries should seek niche markets where they do not have to compete directly with prestigious universities from developed countries.